Архівні документи про “чорні дошки” як знаряддя радянського геноциду в Україні в 1932–1933 роках - Папакін, Г. (Архіви України, 2008)
Based on archival documents, the article reveals the mechanisms and peculiarities of a repressive measure with regard to populated localities, kolhosps (collective farms) and even raions of Ukrainian SSR “blacklisted” in 1932–1933.